2021
DOI: 10.3389/fonc.2021.639060
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of LINC00665 Facilitates the Malignant Progression of Prostate Cancer by Epigenetically Silencing KLF2 Through EZH2 and LSD1

Abstract: This study aimed to explore the function of LINC00665 on the proliferation and metastasis of prostate cancer (PCa), and the potential regulatory mechanisms were also investigated. The expression level of LINC00665 in 50 pairs of PCa tissues and adjacent ones was studied by qRT-PCR, and the associations between LINC00665 and clinicopathological characteristics of PCa patients were analyzed. Control group (sh-NC) and LINC00665 knock-down group (sh-LINC00665) were set in 22RV1 and DU145 cells, respectively. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“… Xue et al (2021) found that LINC00665 was significantly upregulated in prostate cancer tissues and cell lines, and high expression of LINC00665 was correlated with the higher T stage and lymph node metastasis of prostate cancer patients. In addition, they performed the Kaplan-Meier survival analysis and found that the high LINC00665 expression level was associated with the poor survival of prostate cancer patients ( Xue et al, 2021 ). Furthermore, experiments have shown that LINC00665 knockdown inhibited the proliferation, migration, and invasion of prostate cancer cells ( Chen et al, 2020 ; Xue et al, 2021 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 91%
See 4 more Smart Citations
“… Xue et al (2021) found that LINC00665 was significantly upregulated in prostate cancer tissues and cell lines, and high expression of LINC00665 was correlated with the higher T stage and lymph node metastasis of prostate cancer patients. In addition, they performed the Kaplan-Meier survival analysis and found that the high LINC00665 expression level was associated with the poor survival of prostate cancer patients ( Xue et al, 2021 ). Furthermore, experiments have shown that LINC00665 knockdown inhibited the proliferation, migration, and invasion of prostate cancer cells ( Chen et al, 2020 ; Xue et al, 2021 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 91%
“…In addition, they performed the Kaplan-Meier survival analysis and found that the high LINC00665 expression level was associated with the poor survival of prostate cancer patients ( Xue et al, 2021 ). Furthermore, experiments have shown that LINC00665 knockdown inhibited the proliferation, migration, and invasion of prostate cancer cells ( Chen et al, 2020 ; Xue et al, 2021 ). In the process of exploring the mechanism, Chen et al (2020) found a negative correlation between miR-1224-5p and LINC00665 in prostate cancer.…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
See 3 more Smart Citations